2020
DOI: 10.1016/j.xphs.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on Protein Stability During Freezing and Its Impact on the Freeze-Drying Cycle: A Design Space Approach

Abstract: Freezing is widely used during the manufacturing process of protein-based therapeutics, but it may result in undesired loss of biological activity. Many variables come into play during freezing that could adversely affect protein stability, creating a complex landscape of interrelated effects. The current approach to the selection of freezing conditions is however nonsystematic, resulting in poor process control. Here we show how mathematical models, and a design space approach, can guide the selection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 62 publications
1
46
0
Order By: Relevance
“…Moreover, even though economic evaluations have been presented in the past [9][10][11], they are often too broad or too specific to be used for making comparisons between different process strategies. Whereas little effort has been made in this field to determine the economic impact of freeze-drying quantitatively, the optimization of the process has usually remained product-or quality-specific [12][13][14][15][16][17][18], with no considerations of possible bottlenecks in the expenses. In this work, we aim to create a model to evaluate the actual economic impact of a freeze-drying cycle, and evaluate the impact of process parameters on processing costs and, finally, the benefits of process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even though economic evaluations have been presented in the past [9][10][11], they are often too broad or too specific to be used for making comparisons between different process strategies. Whereas little effort has been made in this field to determine the economic impact of freeze-drying quantitatively, the optimization of the process has usually remained product-or quality-specific [12][13][14][15][16][17][18], with no considerations of possible bottlenecks in the expenses. In this work, we aim to create a model to evaluate the actual economic impact of a freeze-drying cycle, and evaluate the impact of process parameters on processing costs and, finally, the benefits of process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…70,93,94 Conformational stability has also been shown to be affected by other stresses, including changes in pH 94 and ionic strength. 95 Furthermore, changes in conformation caused by adsorption onto surfaces, such as ice crystals during freezing, 96 or air bubbles formed by mechanical agitation, 57 is proposed to lead to protein denaturation. 97,98 With regard to colloidal stability, factors that crucially affect repulsive interactions between protein monomers include ionic strength and pH.…”
Section: Strategies For Prevention Of Protein Aggregationmentioning
confidence: 99%
“…As an example, protein therapeutics are often lyophilized to keep them stable during storage and transportation, a process that can result in aggregation via cold denaturation 69,70 or by surface interaction with the ice-water interface. 96 However, the lyophilization process and/or formulation can be optimized, to minimize aggregate formation. To prevent aggregation during freeze-drying a recent study demonstrated how changing to a fast freezing procedure reduced aggregation and loss of activity of a model protein (myoglobin), which is sensitive to cold denaturation.…”
Section: Strategies For Prevention Of Protein Aggregationmentioning
confidence: 99%
See 2 more Smart Citations